Regular use of dental services among university students in southern Brazil - Mariana Silveira Echeverria; Alexandre Emidio Ribeiro Silva; Bernardo Antônio Agostini; Helena Silveira Schuch; Flávio Fernando Demarco (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To verify the prevalence and factors associated with regular use of dental services in university students of the Universidade Federal de Pelotas (UFPel). METHODS This cross-sectional study interviewed 1,865 students aged 18 years or older, starting bachelor's degrees in 2017, enrolled in the second academic semester of 2017 and in the first of 2018 in classroom courses at UFPel. We considered regular users those who reported regularly going to the dentist with or without perceived dental problems. To test factors associated with regular use of dental services, demographic, socioeconomic and oral health variables were collected. Statistical analyses were based on Poisson regression models. RESULTS The prevalence of regular use of dental services was 45.0% (95%CI 42.7-47.3). University students of high economic class (PR = 1.47; 95%CI 0.91-2.36), with last private dental appointment (PR = 1.29; 95%CI 1.03-1.61), positive self-perception of oral health (PR = 2.33; 95%CI 1.79-3.03) and no report of toothache in the last six months (PR = 1.22; 95%CI 1.03-1.45) showed higher prevalence of regular use of dental services. CONCLUSION The results point to inequalities in the regular use of dental services related to socioeconomic factors and a lower use among university students with worse oral health conditions. These results suggest that public health prevention and promotion policies in higher education institutions must be carried out to ensure quality of life among these young adults.